PENDUGAAN POTENSI KARBON TUMBUHAN BAWAH DAN SERASAH DI ARBORETUM UNIVERSITAS LANCANG KUNING - Nofrianto, Nofrianto; Ratnaningsih, Ambar Tri; Ikhwan, Muhammad (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
This study aims to predict or predict the carbon potential stored in undergrowth and litter at the Lancang Kuning University Arboretum. This research was conducted at Arboretum of University of Lancang Kuning and at Faculty of Forestry Laboratory of University of Lancang Kuning. Based on the research that has been done, the potential of wet biomass in the Arboretum of University of Lancang Kuning is 24.39 ton / Ha, and wet biomass of lower plants 2.16 tons / ha. Water content of litter by 52,42% and water content of vegetation below 227,30%. Litter biomass of 15.92 Ton / Ha, and dry vegetable biomass of 0.67 ton / Ha. Level of litter substance by 49,67%, and concentration of fly substance leaf of 51,25%. Litter ash content of 5.58% and lower ash content of 6.24%. Litter carbon content of 44,74%, and carbon content of lower plants by 42,50%. Potential carbon stored in the litter of 7.12 tons / ha and carbon potential stored in plants under 0.28% tons / ha. Lands of carbon potential of litter and vegetation in Arboretum with area of ​​9,2 Ha that is equal to 68,19 ton.